Evaluation of Repair Bond Strenght of Different Repair Methods and Systems to Zirconia Based Ceramics - Altıntaş, Eyyüp; Ayna, Emrah; İzgi, Ayça Deniz (My University, 2022)
Objective: The purpose of this study is to evaluate the bond strength of different repair systems by using composite resin and ceramic cementation repair methods to zirconia-based ceramics. Material and Method: All-ceramic blocks (IPS Empress II; Ivoclar Vivadent, Schaan, Liechtenstein) sized 4.00 mm in length, 5.4 mm in width, and 3.00 mm in height were fabricated by dental laboratory as thirty specimens. CAD/CAM zirconia blocks (n =40) (Prozir; SeramDent, Turkey) sized 5.00 mm in length, 5.4 mm in width and 13.0 mm in height by CEREC System were fabricated from fully sintered Y-TZP core. Zirconia specimens were randomly divided into seven groups for the following different intraoral repair systems(Clearfil, Cimara Zircon, Bisco) and a control group. Every ten specimens were repaired as same sized. Control group was fabricated by conventional firing as unbroken solid zirconia ceramic samples. Each specimen underwent 5000 cycles of thermocycling. The SBSt (Shear bond strength test) was performed by loading force on the repaired piece to record load-to-failure. Failure mode was evaluated using a digital microscope and SEM. SBSt data were analyzed using one-way ANOVA and Tukey’s HSD test. Results: Clearfil and Cimara Zircon systems significantly increased the bond strength for composite resin method when compared with the Bisco system (respectively p <0.001, p =0.001). All-ceramic method significantly increased the bond strength when compared with the composite resin in Bisco system (p <0.001). Conclusion: Although the composite restoration method is effective for repair, the all-ceramic/zirconia repair method can be an option for repairing layered zirconia restorations.
Keywords: Malzeme Bilimleri; Özellik ve Test; İmalat Mühendisliği; Malzeme Bilimleri; Seramik